x → ∞ lim ( 2 x + 1 ) 1 0 ( 2 x − 1 ) 6 ( 3 x − 1 ) 4 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
lim x → ∞ ( 2 x + 1 ) 1 0 ( 2 x − 1 ) 6 ( 3 x − 1 ) 4
= lim x → ∞ ( 2 x + 1 ) 6 ( 2 x + 1 ) 4 ( 2 x − 1 ) 6 ( 3 x − 1 ) 4
= lim x → ∞ ( 2 x + 1 2 x − 1 ) 6 × ( 2 x + 1 3 x − 1 ) 4
= lim x → ∞ ( x ( 2 + x 1 ) x ( 2 − x 6 ) ) 6 × ( x ( 2 + x 1 ) x ( 3 − x 1 ) ) 4
= ( 2 + 0 2 − 0 ) 6 × ( 2 − 0 3 − 0 ) 4
= 1 6 8 1
Simple to complex complex to compoud Easy difficult doesnot matter but to share and learn it matters
An easy one
L = x → ∞ lim ( 2 x + 1 ) 1 0 ( 2 x − 1 ) 6 ( 3 x − 1 ) 4 = x → ∞ lim ( 2 + x 1 ) 1 0 ( 2 − x 1 ) 6 ( 3 − x 1 ) 4 = 2 1 0 2 6 3 4 = 1 6 8 1 Divide up and down by x 1 0
Problem Loading...
Note Loading...
Set Loading...
x → ∞ lim ( 2 x + 1 ) 1 0 ( 2 x − 1 ) 6 ( 3 x − 1 ) 4 =
x → ∞ lim ( 2 x ) 1 0 ( 2 x ) 6 ( 3 x ) 4 =
x → ∞ lim ( 2 1 0 ) ( x 1 0 ) ( 2 6 ) ( x 6 ) ( 3 4 ) ( x 4 ) =
x → ∞ lim [ 2 1 0 ( 2 6 ) ( 3 4 ) × x 1 0 x 1 0 ] =
x → ∞ lim 2 4 3 4 =
x → ∞ lim 1 6 8 1 =
1 6 8 1